Long-term shedding and clonal turnover of enterohemorrhagic Escherichia coli O157 in diarrheal diseases. - Karch, H (1995)
To investigate the length of time that Shiga-like toxin-producing Escherichia coli O157 is excreted after the onset of diarrhea, 456 serial stool specimens were obtained from 53 children. E. coli O157 cells were identified by the use of DNA probes followed by agglutination with a specific antiserum. Specimens were collected until three consecutive stool samples (collected within 9 days) were negative for E. coli O157. The median durations of shedding were 13 days (range, 2 to 62 days) in patients with diarrhea or hemorrhagic colitis and 21 days (range, 5 to 124 days) in patients that developed hemolytic uremic syndrome. In 36 (68%) of the patients, only the first culture was O157 positive, and the three cultures that followed were negative. In 7 (13%) of the patients, E. coli O157 cells were shed for more than 32 days after the onset of diarrhea; these long-term shedders were clinically asymptomatic by the end of this period. In 12 patients, one or two serial O157-negative cultures, obtained up to 8 days after a positive culture, were followed by another positive culture. Comparison of the first and last E. coli O157 isolates by pulsed-field gel electrophoresis revealed that in three of the seven long-term shedders, pulsed-field gel electrophoresis types varied. In two cases, a Shiga-like toxin gene was apparently lost during infection. The observation of long-term shedding accompanied by genotypic turnover has epidemiological and diagnostic implications.